Indonesian Cultural Diplomacy in the United States Through the House of Culture - Samuel Adolfo Mariano Sanam (Eduvest - Journal of Universal Studies, 2025)
Rumah Budaya Indonesia represents one of the instruments utilized by the Indonesian government to enhance its soft power, with the objective of establishing cultural diplomacy relations with the United States. This research examines the cooperative relations in the social and cultural fields between Indonesia and the United States. Over time, Indonesian cultural values must be preserved and promoted. The Indonesian government adopted a strategic policy through the establishment of cultural centers in the form of Rumah Budaya Indonesia in the United States to continuously promote Indonesian culture. This research employs qualitative methods with a prospective case study approach to analyze the question: “How are the efforts of Indonesian cultural diplomacy in the United States through Rumah Budaya Indonesia in increasing Indonesia’s soft power?” In addressing this research question, the writer applies the concepts of soft power and cultural diplomacy. The findings indicate that the development of Rumah Budaya Indonesia in the United States can be differentiated through aspects of quality and quantity, including building infrastructure, technological capacity, service quality, visitor target percentages, and the distribution of Rumah Budaya Indonesia across various states in the United States. Furthermore, through various arts, festivals, and culinary activities organized by Rumah Budaya Indonesia, these initiatives help mitigate the negative impacts of the COVID-19 pandemic in previous years, which had disrupted the stability of Indonesia’s soft power presence in the United States.